Raising Ecological Awareness: A Biological Approach to Sustainable Education - Lasaiba, Irvan (JENDELA PENGETAHUAN, 2023)
This study aims to analyze the role of sustainable education in enhancing ecological awareness among the younger generation through a literature review. Within a comprehensive conceptual framework, this research explores the interrelation between sustainable education and ecological awareness, as well as the factors influencing the effectiveness of sustainable education. Literature analysis results indicate that sustainable education positively impacts enhancing ecological awareness among the younger generation. Integrating environmental issues into the curriculum creates opportunities to broaden students' insights into global environmental challenges. Teachers serve as facilitators, encouraging a profound understanding of these issues, while the support and engagement of various stakeholders strengthen the positive impact of sustainable education. This study contributes to shaping ecological awareness among the younger generation